Empowerment of marginal and small farmers need for budgetary support - Hegde, Narayan (Indian Farming, 2019)
As agriculture is the main source of livelihood for a majority of the rural population, dominated by small and marginal farmers, food security of the nation cannot be solved unless these farmers are empowered to enhance their income through agriculture. Although agriculture is a state subject, the Government of India has a major role in supporting the state initiatives through suitable policy measures and financial support through the annual budget. Based on the observations made by various stakeholders directly engaged in agricultural development in the country, the study identified where small and marginal farmers need support immediately.